دابەشبوونی جوگرافی بەست و بەنداوەکانی سەر هەردوو لقی زێی بچوک و سیروان لە وڵاتی ئێراندا - خضری, سعید محمد حمزە; علاءالدین, عطا محمد; محمد, سەرهەد طارق (Sulaimani Journal for Humanities, 2022)
Dams are considering as the most significant project on rivers. Specially in this era of time they have huge importance. Therefore, Iran Government built several dams on the Sirwan and little zab river to reserve and use their water for Drinking, agriculture and provide water security for the country. These projects have short and long term affects in present and future. In this research the geographical distribution of the dams has been explained, also the capacity of the rivers and the area that has been covered by them has been Showed.
Keywords: Dams; Geographical distribution; Area; Water Storage Capacity